Differential effect of nine cinnamic acid derivatives on the biocatalytic activity of Candida antarctica lipase type B - Zappaterra, Federico; Meola, Domenico; Presini, Francesco; Aprile, Simona; Venturi, Valentina; Nosengo, Chiara; De Luca, Chiara; Catani, Martina; Lerin, Lindomar Alberto; Giovannini, Pier Paolo (Current Research in Biotechnology, 2024)
Naturally occurring cinnamic acid derivatives are a broad family of aromatic carboxylic acids with bioactive properties. Among the cinnamic acid derivatives, for instance, are ferulic acid and caffeic acid, which have been widely studied for their antioxidant and anti-inflammatory properties. These active ingredients are mostly poorly soluble in water, which greatly limits their bioavailability. To increase the bioavailability of these acids, green esterification protocols can be developed exploiting lipases. In particular, this article reports the process optimization for the enzymatic esterification of nine cinnamic acid derivatives with erythritol, a polyol highly soluble in water. The study explores how the different substituents present on the aromatic ring of the cinnamic acid derivatives affect the catalytic capacity of the Candida antarctica lipase type B. The study, conducted through both molecular docking and experimental evidence, shows how hydroxyl groups on the aromatic ring can strongly limit the conversion of the acids to the corresponding esters. At the same time, the degree of unsaturation of the derivative also influences the favorable poses in the active site of the lipase. The best results (yields over 95 %) were obtained with 10 g/L of lipase, a temperature of 90 ◦C, molar ratio (acid/alcohol) of 3:1, for 72 h of reaction time.